MULTISENSORY EXPERIENCE IN THE OUTDOOR DESIGN OF TAMAN TRUNOJOYO MALANG - Sari, Komang Ayu Laksmi H; Winarni, Sri; Pramitasari, Putri Herlia; Biladt, Heickal Muhammad Aqil (Border: Jurnal Arsitektur, 2022)
The user's sensory experience of an architecture evokes his emotions. The sensory system is not only limited to the visual aspect, but of course other senses. Human perception is basically multisensory, so that the individual will easily explain experiences through previous environmental interactions. This research was conducted to examine the user's multisensory experience at Taman Trunojoyo regarding the architectural space elements. The method used is descriptive qualitative, data collection using literature study and observation. This study divides the four areas studied and analyzes the architectural elements in terms of visual, haptic, auditory, olfactory and basic orientation aspects. In addition, the application of the parameters of the movement plane, guiding plane and resting plane were also analyzed in each area. The results of this study indicate that Trunojoyo park is not limited to a park that can only be enjoyed visually, but this park provides elements that can provide a multisensory experience to visitors. Such as the facilities of a reflection garden, elements of a fountain and children's playground, and others. However, because of its location in the middle of the city, it causes disturbances such as vehicle noise that enters at several points in the area.